Serotype distribution, antibiotic resistance pattern, and multilocus sequence types of invasive Streptococcus pneumoniae isolates in two tertiary pediatric hospitals in Beijing prior to PCV13 availability - Wei Shi; Jing Li; Fang Dong; Suyun Qian; Gang Liu; Baoping Xu; Lin Zhou; Wenjian Xu; Qinghong Meng; Qing Wang; Kunling Shen; Lijuan Ma; et al. (Taylor & Francis Group, 2019)
Background: Invasive pneumococcal disease (IPD) is a serious threat to children worldwide. This study reported the serotype distribution, antibiotic resistance pattern, and multilocus sequence types of 111 IPD strains isolated from children less than 14 years old in two tertiary pediatric centers in Beijing during the years 2012-2017. Methods: Serotypes were determined using Quellung reaction. Antibiotic resistance was tested using the E-test or disc diffusion method. Sequence types (STs) were assigned via multilocus sequence typing. Results: The most common serotypes of the IPD isolates were 19F, 19A, 14, 23F, and 6B, and the PCV13 coverage rate was 90.1%. For the meningitis isolates, the resistance rate to penicillin was 95.7%, and the non-susceptibility rate to ceftriaxone was 65.2%. All of the non-meningitis isolates were susceptible to penicillin, and the susceptibility rate to ceftriaxone was 89.8%. All but one of the isolates were highly resistant to erythromycin. The multidrug resistance rate of all isolates was 89.2%. The most common STs were ST320, ST271, ST876, and ST81, which belonged to serotype 19A, 19F, 14, and 23F, respectively. Conclusion: Given the high coverage rate of PCV13 and the worrisome non-susceptibility rate of IPD isolates to antibiotics, PCV13 use would be beneficial for Chinese children.